Comparative screening of enzyme producing endophytic actinomycetes from fresh and fallen leaves of Emblica officinalis in Western Ghats - Singh, Mrinalini; Sedhuraman, Padmavathy (International Journal of Biological Research, 2014)
Objective: To assess the comparative amylase, lipase and cellulase production abilities of endophytic actinomycetes isolated from both fresh and fallen leaves of Emblica officinalis in Western Ghats. Methods: Endophytic actinomycetes were isolated using Starch casein agar media. The screening of these isolates for extracellular enzymatic production was carried out using carbohydrate degradation test. Results: Among the endophytic actinomycetes isolated from fresh leaves, 75% exhibited amylase activity, 41.66% exhibited lipase activity and 50% exhibited cellulase activity whereas in fallen leaves, 80% exhibited amylase activity, 60% exhibited lipase activity and 60% exhibited cellulase activity. Conclusion: Hence, endophytic actinomycetes isolated from the fallen leaves exhibited remarkable lipase, cellulase and amylase producing capacity which mediates as biocatalysts in bioremediation and biofuel production, as compared to fresh leaves. Keywords: Amylase, Lipase, Cellulase, Endophytic Actinomycetes, Emblica officinalis, Western Ghats.